Correction of estrogen deficiency states in women with endometriosison the background of therapygonadtropin-releasing hormone - N A Tatarova; A M Marzhevskaya; N P Gavrilova; L V Savina (IP Berlin A.V., 2013)
Research objective. Development of a program of correction of neurovegetative symptoms of climacteric syndrome in patients with estrogen deficiency, to prove the effectiveness of b-alanine in acute attacks of hot flashes and heat in patients of reproductive age, who use therapy agonist of gonadotropin-releasing hormone and the low level of estrogen.The study involved women 2 groups: group 1 - patients with adenomyosis and external genital endometriosis 3 - grade 4, a total of 78 patients; 2nd group - control (30 people with the same diagnosis).Patients in groups 1 and 2 were treated for 6 months triptorelininjection of 3,75 mg (1 injection per month), for 2-3 months of treatment were seen estrogen deficiency symptoms: hot flashes, sweating, tachycardia. At 3 months, all patients of group 1 was assigned to b-alanine at a dose 800 mg/day, the duration of receiving b-alanine 3 months. The control group is the patients refused the correction of b-alanine symptoms of menopausal syndrome. To assess the severity of symptoms of menopausal syndrome was used modified menopausal index (MMI).Control estrogen deficiency implemented by measuring the serum estradiol level (pg/L).Results. After 6 months of treatment was obtained by statistically significant (p